Impact of Factors upon Children’ Weight Status of age one to Five years old at Primary Health Care Centers in AL Samawah City - talib, abrar; Abdulwahd, hala (Iraqi National Journal of Nursing Specialties, 2019)
Objective: The study aim is to identify factors that may contribute to children’s weight status variations. Methodology: A descriptive cross sectional study is carried out has been conducted at the AL- Samawah city in Primary Health Care Centers for the purpose of the screening children’s weight status of Age One to five Years Old. This study is started from December 16th 2018 to February 14th 2019. A(non propriety) purposive sample comprised of (20) primary health centers (10 main and 10 sub) are selected of 500 children who visit the primary health care center during the period for the purpose of the study; Data was collected through using a questionnaire designed and developed for the purpose of the study . It consists of two main parts: Part I. Mother Demographic Characteristics, Medical and Surgical History during Pregnancy, Obstetric History and Mothers Nutrition during Pregnancy and Lactation. . Part II: Childes Demographic Characteristics, Medical and Surgical History, Immunization, and Child Nutrition. Data collected by the researcher from children’s families through interview and filling a questionnaire format, while the section of anthropometric measurements carried out by the researcher after measuring weight and height doing Body Mass Index calculation Validity of the study instrument was determined through a panel of experts and reliability of the instrument was determined. The analysis of the data used was descriptive statistics and statistical inferential. Recommendations: The ministry of health can develop and implement effective strategies for the detection and treatment of malnutrition among children.